Validity of the Good Practice Guidelines: The example of type 2 diabetes. (November 2020) - Tudrej, Benoit V.; Favard, Delphine; Vaillant-Roussel, Hélène; Pouchain, Denis; Jaafari, Nemat; Boussageon, Rémy
Highlights: Good Practice guidelines for treatment of type 2 diabetes are of poor quality and their methodological rigors are insufficient. Good Practice Guidelines should be more precise about their search strategy and should systematically indicate: the research period, the key words and the databases used for the literature review, and a complete explanation for the reasons for inclusion or exclusion of studies with a high level of evidence. Abstract: Aims: To assess the methodological quality of the systematic reviews of the literature for Good Practice Guidelines (GPGs) for treatment of type 2 diabetes (T2D). Methods: The GPGs on treatment of T2D from May 2012 onwards were searched on PubMed, the Guidelines International Network, the National Guidelines Clearing House and the Infobanque des guides de pratique clinique . Quality of the GPGs was assessed by means of grading of levels of evidence, strength of recommendations, statements pertaining to systematic reviews, description of their methods, search for Randomized Controlled Trials meta-analyses, and citations from three meta-analyses which contested the strategy of intensive glycemic control and metformin as first-line treatment. Results: Fiflty-two GPGs were included; half of them had and applied a system of grading and strength of recommendation and 58% stated they had carried out a systematic review. Only one GPG cited the three meta-analyses. Three quarters of the GPGs failed to detail their bibliographic research methods. Conclusion: The GPGs for treatment of T2D were of poor quality and their methodological rigor was insufficient. Even though the meta-analyses had a higher level of evidence, they were seldom cited.